2021
DOI: 10.1002/advs.202102178
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Flexible Freestanding BiMnO3 Membranes with Stable Ferroelectricity and Ferromagnetism

Abstract: Multiferroic materials with flexibility are expected to make great contributions to flexible electronic applications, such as sensors, memories, and wearable devices. In this work, super-flexible freestanding BiMnO 3 membranes with simultaneous ferroelectricity and ferromagnetism are synthesized using water-soluble Sr 3 Al 2 O 6 as the sacrificial buffer layer. The super-flexibility of BiMnO 3 membranes is demonstrated by undergoing an ≈180°folding during an in situ bending test, which is consistent with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…[84] Many polymer materials have been developed and used as support layers, considering the merits of flexibility, mechanical strength, and adhesive contact, such as polyimide (PI) tape, polydimethylsiloxane (PDMS), [11,12,82,87] polymethyl-methacrylate (PMMA), [20,62] polystyrene (PS), or the combination of these materials, like polypropylene carbonate (PPC)-PDMS stack [13,62,87] and PI sheet with PPC layer. [52,67] PMMA, which is most commonly used in transferring of chemical-vapor-deposited graphene, [38,84] has also found a wide application in the transfer of oxide membrane. [20,62,42] PMMA can be easily coated on the oxide surface, and washed away by acetone once the transfer is completed, see Figure 3a.…”
Section: Transfer Methods For Freestanding Oxide Thin Filmsmentioning
confidence: 99%
See 4 more Smart Citations
“…[84] Many polymer materials have been developed and used as support layers, considering the merits of flexibility, mechanical strength, and adhesive contact, such as polyimide (PI) tape, polydimethylsiloxane (PDMS), [11,12,82,87] polymethyl-methacrylate (PMMA), [20,62] polystyrene (PS), or the combination of these materials, like polypropylene carbonate (PPC)-PDMS stack [13,62,87] and PI sheet with PPC layer. [52,67] PMMA, which is most commonly used in transferring of chemical-vapor-deposited graphene, [38,84] has also found a wide application in the transfer of oxide membrane. [20,62,42] PMMA can be easily coated on the oxide surface, and washed away by acetone once the transfer is completed, see Figure 3a.…”
Section: Transfer Methods For Freestanding Oxide Thin Filmsmentioning
confidence: 99%
“…[22,30] Indeed, it was shown that single-crystal perovskite membranes can sustain extremely large tensile strain before breaking. [22,69,30,35,38,122] In particular, Harbola et al showed that in single-crystal membranes of STO the tensile strain strength can be as high as 6%, almost an order of magnitude more than in bulk form. [22] A nonmonotonic change of the Young modulus in nanometric membranes of STO was also observed, due to a competitive behavior of surface elasticity and strain gradient elasticity.…”
Section: Enhanced Elasticity and Flexibilitymentioning
confidence: 99%
See 3 more Smart Citations